รูปแบบการบริหารวิชาการสำหรับโรงเรียนอนุบาล THE DEVELOPMENT OF AN ACADEMIC MANAGEMENT MODEL FOR KINDERGARTEN SCHOOLS - orapiriyakul, supak; ศิริบรรณพิทักษ์ พฤทธิ์; อุสาโห ชญาพิมพ์ (Journal of Education Studies, Chulalongkorn University, 2014)
การวิจัยครั้งนี้ใช้ระเบียบวิธีวิจัยเชิงบรรยาย วัตถุประสงค์เพื่อศึกษาสภาพปัจจุบันและสภาพที่พึงประสงค์ของรูปแบบการบริหารวิชาการของโรงเรียนอนุบาล ประชากรที่ศึกษา คือ ผู้บริหาร/ครูของโรงเรียนที่มีการจัดการเรียนการสอนระดับอนุบาล จำนวน ๓๖,๑๙๒ โรง กลุ่มตัวอย่าง คือ ผู้บริหาร/ครูของโรงเรียนที่มีการจัดการเรียนการสอนระดับอนุบาล จำนวน ๓๙๖ โรง โดยการสุ่มแบบหลายขั้นตอน ผู้ให้ข้อมูลประกอบด้วย ผู้อำนวยการโรงเรียน รองผู้อำนวยการฝ่ายวิชาการ หัวหน้าระดับปฐมวัย/ครู ได้รับข้อมูลกลับคืนจำนวน ๓๗๑ โรง รวม ๑,๑๑๒ ชุด คิดเป็นร้อยละ ๙๓.๖๙ เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม แบบสัมภาษณ์ สถิติที่ใช้คือ ค่าความถี่ ร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า สภาพปัจจุบันและสภาพที่พึงประสงค์ของการบริหารวิชาการโรงเรียนอนุบาล โดยภาพรวมของการบริหารหลักสูตรสถานศึกษา การจัดการเรียนการสอน และการวัดผลและประเมินผล พบว่า รูปแบบการบริหารงานแบบเพื่อนร่วมงานมีมากที่สุด คือ ร้อยละ ๕๘.๓๓ รองลงมามีค่าเท่ากัน คือ รูปแบบการบริหารแบบทางการและการบริหารแบบการเมือง ร้อยละ ๒๐.๘๓ The objectives of this research were to study the current and the desired academic management methods for kindergarten schools. The population contains a total of 36,192 schools. From the population, 396 schools (by multi-step sampling). A total of 1,112 questionnaires were sent to the sample group; responses were received from 371 schools (93.69%). The schools’ headmasters, deputy directors of academic activities and early childhood teachers were the data providers. The instruments used in this research consisted of questionnaires and structured interview. The parameters used for the statistical analysis of the quantitative data included mean (xˉ), percentile (%), frequency (f) and standard deviation (S.D.). Research found: In the study on the current and desired academic management models with regard to educational curriculum, learning experience, and assessment and evaluation; it was found that the most desirable model is the Collegial Model at the percentage of 58.33, followed by the Formal Model and political model at the percentage of 20.83.